Income inequality and depression among Canadian secondary students: Are psychosocial well-being and social cohesion mediating factors? - Claire Benny; Karen A. Patte; Paul Veugelers; Scott T. Leatherdale; Roman Pabayo (Elsevier, 2022)
Background: Nearly one-third of secondary school students report experiencing depressive symptoms in the past year. Existing research suggests that increasing rates of depression are due in part to increasing income inequality. The aim of this study is to identify mechanisms by which income inequality contributes to depression among Canadian secondary school students. Methods: We used data from a large sample of Canadian secondary school students that participated in the 2017/18 wave of the Cannabis, Obesity, Mental health, Physical activity, Alcohol, Smoking, and Sedentary behaviour (COMPASS) study. The sample included 61,642 students across 43 Census divisions (CDs) in Quebec, Ontario, Alberta, and British Columbia. We used multilevel path analysis to determine if the relationship between CD-level income inequality and depression was mediated by student's psychosocial well-being and/or social cohesion. Results: Attending schools in CDs with higher income inequality was related to higher depression scores among Canadian secondary students [unstandardized ß (ß) = 5.36; 95% CI = 0.74, 9.99] and lower psychosocial well-being (ß = −14.83, 95% CI = −25.05, −4.60). Income inequality was not significantly associated with social cohesion, although social cohesion was associated with depression scores among students (ß = −0.31; 95% CI = −0.34, −0.28). Discussion: Findings from this study indicate that income inequality is associated with adolescent depression and that this relationship is mediated by psychosocial well-being. This study is the first of its kind in Canada to assess the mechanisms by which income inequality contributes to adolescent depression. These findings are applicable to school-level programs addressing mental health.